Randomized phase II study of a bendamustine monotherapy schedule for relapsed or refractory low-grade B-cell non-Hodgkin lymphoma or mantle cell lymphoma (RABBIT-14). Issue 7 (3rd July 2018) - Itoh, Kuniaki; Igarashi, Tadahiko; Irisawa, Hiroyuki; Aotsuka, Nobuyuki; Masuda, Shinichi; Utsu, Yoshikazu; Tsujimura, Hideki; Tsukasaki, Kunihiro; Wakita, Hisashi
Abstract: The aim of this randomized phase II study was to improve the treatment delays and discontinuations associated with bendamustine use by comparing the effect of Benda-14 (intravenous bendamustine, 120 mg/m 2 on days 1 and 15, repeated every 4 weeks for a total of 6 cycles) with those of the standard treatment in relapsed indolent lymphoma and/or mantle cell lymphoma. Forty-six patients were randomly assigned to the treatments from September 2012 to February 2016. Treatment accomplishment rate and median relative dose intensity were similar in both arms: 38 and 63.4% in the Benda-14 arm and 41 and 66.3% in the standard treatment arm, respectively. The overall response rate and median progression-free survival, respectively, were 83% and 21.0 months for Benda-14, and 77% and 15.5 months for the standard treatment. Benda-14 induced favorable responses with less frequent hematological toxicities.